An evaluation of the potential drug interaction between warfarin and levothyroxine. (25th June 2014) - Wood, M. D.; Delate, T.; Clark, M.; Clark, N.; Horn, J. R.; Witt, D. M.
Summary Background Drug interaction references report that initiation of levothyroxine potentiates the effects of warfarin, and recommend more frequent International Normalized Ratio (INR) monitoring, but the mechanism is not well understood. Objective To assess the impact of levothyroxine initiation on INR response. Patients/Methods A retrospective, self‐controlled study was performed on patients aged ≥ 18 years receiving chronic warfarin therapy who were started on levothyroxine between 1 January 2006 and 30 June 2013, and who were followed for 90 days prior to and after levothyroxine initiation. The included patients had at least one elevated thyroid‐stimulating hormone laboratory value in the pre‐period, continuous warfarin therapy for 100 days prior to levothyroxine initiation, no purchases of medications known to interact with warfarin, no procedures requiring warfarin interruption, and no bleeding or thromboembolic event during the study period. The primary outcome was a comparison of the warfarin dose/INR ratio recorded before the initiation of levothyroxine with the ratio recorded during the post‐period after two consecutive INRs with no warfarin dose change. Results One hundred and two patients were included in the primary outcome. The mean warfarin dose/INR ratios in the pre‐period and post‐period were equivalent (P = 0.825). Although the mean warfarin dose was numerically lower in the post‐period than in the pre‐period, this difference did not reach statistical significance (P = 0.068). Conclusion No difference in the mean warfarin dose/INR ratio before and after initiation of levothyroxine was detected. The results suggest that there is not a clinically significant interaction between warfarin and levothyroxine, and so additional monitoring may not be necessary.